2023
DOI: 10.1177/0192513x221150995
|View full text |Cite
|
Sign up to set email alerts
|

Types of Family Leisure Activities in Families With Adolescents

Abstract: Leisure has been acquiring a leading role in families to the point of being represented in different areas of society. In fact, a diversified practice is necessary to obtain maximum benefit. Thus, the purpose of this study was to examine which are the types of family leisure activities most exercised. The degree of frequency of 11 types of family leisure activities was measured on a four-point Likert scale. The same consisted of 1054 Compulsory Secondary Education students from the southeast of Spain. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(48 reference statements)
0
4
0
2
Order By: Relevance
“…Un análisis más detallado de los resultados evidencia que el ocio deportivo y turístico-cultural son las modalidades que más sobresalen en la familia. Esta relación entre familia y ocio deportivo se ha consolidado en los últimos años (Álvarez-Muñoz & Hernández-Prados, 2023;Fraguela et al, 2020;Sarrate, 2008). Al respecto Haycock y Smith (2014) señalaron que las probabilidades de adquirir hábitos y valores deportivos aumentaron, sobre todo si ambos progenitores tienen integrado el deporte en sus vidas, aunque se encuentran condicionadas por las limitaciones financieras y de transporte.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Un análisis más detallado de los resultados evidencia que el ocio deportivo y turístico-cultural son las modalidades que más sobresalen en la familia. Esta relación entre familia y ocio deportivo se ha consolidado en los últimos años (Álvarez-Muñoz & Hernández-Prados, 2023;Fraguela et al, 2020;Sarrate, 2008). Al respecto Haycock y Smith (2014) señalaron que las probabilidades de adquirir hábitos y valores deportivos aumentaron, sobre todo si ambos progenitores tienen integrado el deporte en sus vidas, aunque se encuentran condicionadas por las limitaciones financieras y de transporte.…”
Section: Discusión Y Conclusionesunclassified
“…Aunque en esta etapa del desarrollo evolutivo se produce el desenganche familiar, el ocio actúa como elemento de encuentro intergeneracional. Algunas de las tipologías de ocio familiar más comunes durante la adolescencia son: deportiva, ante la generalización de modelos de vida saludable a las dinámicas familiares (Sala Bustos, 2020); digital, pues la presencia de las TIC en la sociedad y educación se hace extensible a los hogares y las formas de recreación promoviendo una transformación de los estilos de vida (Caballo et al, 2012;; y, también, desde lo tradicional, el ocio familiar turístico como uno de las prácticas más recurrentes que se han reconvertido y diversificado en los últimos años (Álvarez-Muñoz & Hernández-Prados, 2023). Además, el ocio familiar se encuentra condicionado por variables como el género, edad y etapa educativa del menor (Álvarez, 2020); el nivel de estudios y ocupación laboral parental (Hernández-Prados & Álvarez-Muñoz, 2022); el lugar de residencia, pues el adolescente rural encuentra una oferta más limitada de ocio consumista, ya que los grandes centros comerciales se sitúan en la ciudad (Maroñas et al, 2019).…”
Section: Introductionunclassified
“…Finally, they may differ in their approach. Among the most practised family leisure activities with adolescents are sports, cultural, therapeutic, digital, and naturalistic leisure ( Álvarez Muñoz and Hernández Prados, 2023 ).…”
Section: Family Leisure and Adolescent Autonomy Developmentmentioning
confidence: 99%
“…Unstructured activities lack adult supervision and typically take place in public spaces, without a specific skill development objective, but rather emphasizing socialization ( Ibabe et al, 2023 ). Some of the most commonly practised family leisure activities fall into this category, such as gastronomic leisure, digital leisure, and commercial leisure ( Álvarez Muñoz and Hernández Prados, 2023 ). However, these activities receive comparatively less attention in the literature ( Marshall et al, 2014 ).…”
Section: Family Leisure and Adolescent Autonomy Developmentmentioning
confidence: 99%
“…Extensive research has demonstrated the impact of the family environment on the formation of exercise habits among adolescents (Mota, 1998 ; Zovko et al, 2021 ). For example, factor such as family support (Kuo et al, 2007 ; Álvarez Muñoz and Hernández Prados, 2023 ; Hu and Cai, 2023 ), parental role modeling (Adkins et al, 2017 ; Do et al, 2023 ), and the availability of resources and opportunities for physical activity within the family context (Álvarez Muñoz and Hernández Prados, 2023 ) have been found to be crucial in influencing adolescents' exercise behaviors. The family environment encompasses various aspects, including parental attitudes (Cleland et al, 2011 ; Whooten et al, 2023 ), parental involvement (Kuo et al, 2007 ), family socioeconomic status (Cleland et al, 2011 ), and the home physical activity environment (Kuo et al, 2007 ; Cleland et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%